ANALISIS PERENCANAAN KEBUTUHAN BAHAN BAKU DARI PRODUK SUSU SGM SEREAL BERAS MERAH DENGAN MEMPERTIMBANGKAN KAPASITAS PRODUKSI, WAKTU KADALUWARSA BAHAN DAN FAKTOR INCREMENTAL DISKON - Yuliastuti Ramadhani; Imam Sodikin (Jurnal Teknologi, 2009)
Inventory problem in manufacturing system can not be avoid. In food and drink industrial have need material inventory, because material inventory seriously to determined smooth. Production process, but much inventory will spent any cost. To avoid that need research to minimize purchasing cost with advantage discount factor much more material that ordered louse reach discount, will give effect amount saved so much and so long that will loused material that saved become expired, even it is increase total inventory cost. One of method which can be used to control the inventory is method EOQ. EOQ method incremental discount is order method that able to minimize total inventory cost based on discount level that ordered. This research aim to determine the amount of ordering and frequency of ordering raw material pursuant to capacity produce by considering factor discount and also expired time material. Based research result expired time influence at inventory system, material purchasing that that so much, it caused reach cutting price is discount in not usually giving profit, coused as much material that borght, purchase will much also material that expired, this is give effect, high total inventory cost.